2005
DOI: 10.1038/sj.ejcn.1602294
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in healthy older European adults: the ZENITH study

Abstract: Objective: Baseline data are reported from a study of the effects of zinc supplementation on cognitive function in older adults as assessed by the CANTAB computerised test battery. Design: This is a multicentre prospective intervention study employing a randomised double-blind design. Setting: European community-based study. Participants: There are 387 healthy adults aged 55-87 y from centres in France, Italy and Northern Ireland. Interventions: Measures of visual memory, working memory and attention were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The results are more evident when the zinc status indicates a deficiency of this trace element. In agreement with previous findings, which indicated that zinc is of benefit for psychological aspects in older adults Simpson et al 2005;McConville et al 2005), significant differences in zinc status and psychological dimensions were found among the five Countries herein considered.…”
Section: Discussionsupporting
confidence: 93%
“…The results are more evident when the zinc status indicates a deficiency of this trace element. In agreement with previous findings, which indicated that zinc is of benefit for psychological aspects in older adults Simpson et al 2005;McConville et al 2005), significant differences in zinc status and psychological dimensions were found among the five Countries herein considered.…”
Section: Discussionsupporting
confidence: 93%
“…E2014Tt, 49.41 cm diagonal display area, maximum resolution of 1600×900 pixels at 60 Hz), following standard procedures in accordance with the user's manual and as previously described (9,14,15,20). CANTAB tests use non-verbal stimuli for cognitive assessment, and include a practice section that does not count towards the final score.…”
Section: Methodsmentioning
confidence: 99%
“…24 In the Zenith study, a multicentre prospective intervention study employing a randomized double-blind design, 387 healthy adults aged 55-87 years were treated with 15 mg Zn, 30 mg Zn, or placebo for 6 months. 34,39 Visual memory, working memory, attention, and reaction time were measured at baseline, after 3 and 6 months. Zn supplementation was associated with improved scores in tests on attention and spatial working memory (two of the eight cognitive tests).…”
Section: Supplementation Of Znmentioning
confidence: 99%